Autophagy Regulates the Survival of Hair Cells and Spiral Ganglion Neurons in Cases of Noise, Ototoxic Drug, and Age-Induced Sensorineural Hearing Loss - Guo, Lingna; Cao, Wei; Niu, Yuguang; He, Shuangba; Chai, Renjie; Yang, Jianming (Frontiers in Cellular Neuroscience, 2021)
Inner ear hair cells (HCs) and spiral ganglion neurons (SGNs) are the core components of the auditory system. However, they are vulnerable to genetic defects, noise exposure, ototoxic drugs and aging, and loss or damage of HCs and SGNs results in permanent hearing loss due to their limited capacity for spontaneous regeneration in mammals. Many efforts have been made to combat hearing loss including cochlear implants, HC regeneration, gene therapy and antioxidant drugs. Here we review the role of autophagy in sensorineural hearing loss and the potential targets related to autophagy for the treatment of hearing loss.